Estudio preliminar para la línea ferroviaria de alta velocidad para el tramo Trujillo – Lima bajo un enfoque integral en su planteamiento - Rodriguez Agreda, Jose Antonio (2019)
In this paper, the main objective was the preliminary study of the High Speed Rail Line - LIFAVE, included in the Trujillo - Lima section, constituted under an integral approach in its development, which was based on the use of the hierarchical analytical process - PAJ, as a percentage measurement instrument between LIFAVE and road transport (conventional transport). The process was carried out in parallel under five fronts: the preliminary design of the LIFAVE was developed, which led to the use of thirteen digital elevation models (ASTER GDEM) designed by NASA and the Ministry of Economy, Trade and Industry of Japan (METI) ), then delimited and geo processed the data in the ArcGis and AutoCAD Civil 3D softwar, obtaining as a result the plant design of the LIFAVE axis; the socioeconomic study was carried out, considering six points of analysis (travel time, road safety, intermodality, stations, quality in the service and capacity, and tourist areas); the environmental study was carried out considering three points of analysis (environmental pollution under the global warming approach, impact on protected natural areas, and occupation of soils and barrier effect); the construction cost of the LIFAVE was estimated, having as a base factor the general cost per linear kilometer constructed; The integral study of conventional transport was carried out, where the same analysis points of the LIFAVE were considered. Subsequently, the numerical calculation of the valuation was made (base 10 units) in direct relation to the aforementioned points and criteria, resulting in the socioeconomic criterion 7.7 units for LIFAVE and 2.3 units for conventional transport, in the environmental criterion 6.1 units for the LIFAVE and 3.9 units for conventional transport and in the construction cost criterion 1.5 units for the LIFAVE and 8.5 units for the conventional transport, later the PAJ was guided on the basis of the matrix calculation, from which the final global percentages of both were calculated. modes of transport in the process, resulting in a variation of 20% in favor of LIFAVE, concluding that it is a mode of transport preliminarily integral under socioeconomic, environmental and construction cost criteria with respect to conventional transport.